Fatal outcomes of endoscopy: an analysis from the coronerʼs point of view - Lock, Julian J.; Püschel, Klaus (Endoscopy International Open, 2023)
Background and study aims This study was designed to provide a profound analysis of fatalities associated with endoscopic procedures.Methods Protocols of all autopsies performed within 20 years in a large Department of Forensic Medicine were retrospectively analyzed to identify all fatalities directly related to an endoscopic procedure. Data were further specified focusing on the type of endoscopy and the final cause of death.Results Of 22,615 autopsies performed between January 2000 and September 2019, 86 deaths were identified as complications of an endoscopic procedure. The average age of these 86 patients was 70.9 years (66.4 (range, 26–89) in males (n = 35) and 74.1 years (range, 22–94) in females (n = 51)). Endoscopic procedures included 29 endoscopic retrograde cholangeopancreatographies (ERCPs), 27 colonoscopies, 18 percutaneous endoscopic gastrostomy (PEG) tube placements, six gastroscopies, two upper endosopic ultrasonographies, and four transesophageal echocardiographies. ERCPs, colonoscopy and PEG procedures together accounted for 74 of 86 (86 %) endoscopy-related deaths. Focusing on the single procedures, post-ERCP pancreatitis (14/29, 48 %), colonoscopy-associated perforation (24/27, 89 %), and peritonitis after PEG placement (16/18, 88 %) were the most common causes of death.Conclusions Even in the thought-to-be-safe and screening endoscopic procedures fatalities do occur. This study gives an overview of endoscopy-related fatalities, stressing the role of ERCP, colonoscopy, and PEG.